2011
DOI: 10.1063/1.3530587
|View full text |Cite
|
Sign up to set email alerts
|

Domain formation in membranes with quenched protein obstacles: Lateral heterogeneity and the connection to universality classes

Abstract: We show that lateral fluidity in membranes containing quenched protein obstacles belongs to the universality class of the two-dimensional random-field Ising model. The main feature of this class is the absence of a phase transition: there is no critical point and macroscopic domain formation does not occur. Instead there is only one phase. This phase is highly heterogeneous with a structure consisting of microdomains. The presence of quenched protein obstacles thus provides a mechanism to stabilize lipid rafts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 64 publications
10
67
0
Order By: Relevance
“…23 The differential physical state, presumably tension, could be caused by the live cell plasma membrane's interaction with cortical actin 55,65 and may shift the plasma membrane to a point in the phase diagram where the miscibility transition temperature is lower. 66 However, an absolute magnitude of such tension in live cells may be insufficient to consider tension as the sole principle suppressing miscibility phase transition, 67 and template quenched second order miscibility transition, 39,60,63 as observed in our simulations, may deserve more attention. Perturbation by active processes, Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce t he published form of this manuscript, or allow others to do so, for U.S. Government purposes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…23 The differential physical state, presumably tension, could be caused by the live cell plasma membrane's interaction with cortical actin 55,65 and may shift the plasma membrane to a point in the phase diagram where the miscibility transition temperature is lower. 66 However, an absolute magnitude of such tension in live cells may be insufficient to consider tension as the sole principle suppressing miscibility phase transition, 67 and template quenched second order miscibility transition, 39,60,63 as observed in our simulations, may deserve more attention. Perturbation by active processes, Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce t he published form of this manuscript, or allow others to do so, for U.S. Government purposes.…”
Section: Resultsmentioning
confidence: 98%
“…This means that, with a small perturbation, a second order miscibility transition can be quenched, 60 …”
Section: Fcs Simulationmentioning
confidence: 99%
“…If these conditions are not satisfied, standard Ising or randomly dilute Ising behavior is observed instead, see Refs. [51,52]. On the other hand, little is known on how demixing is influenced by the amount of disorder and by its nature (for a polymer matrix some results for the critical-point behavior as a function of the amount of disorder are reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed in Refs. [3,4] that the quenched disorder found in real cells, provided by fixed cytoskeletal proteins, could be the key stabilizing mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…If the heterogeneous domain structure on the cell surface is an equilibrium state, then some stabilizing mechanism is required; the line tension incurred by interfaces between domains would make inhomogeneous phases energetically unfavorable when compared to a fully phase-separated system. Computer simulation studies of simple model systems [3,4] have shown that the size, composition, and dynamics of membrane domains can be regulated by introducing randomly located, immobile objects. These obstacles, embedded within the two-dimensional fluid, serve to hinder macroscopic phase separation and act as a source of quenched disorder.…”
Section: Introductionmentioning
confidence: 99%